DEVELOPMENT OF RURAL TERRITORIES IN LATVIA IMPLEMENTING TELEWORK - Vītola, Alise; Baltiņa, Iveta; Ādamsone, Liena; Judrupa, Ilze; Šenfelde, Maija (Via Latgalica, 2013)
Population decline is taking place in rural areas in Latvia as well as in rural areas in Europe. There is a question of utmost importance - will people choose to live in the rural area doing remote work or will they choose the job in the towns. Increased pace of population declining is forecasted in the event of steady decreasing working places and services. Growing service costs per inhabitant may infl uence lowering of accessibility of some services in the territory. Till nowadays measurements of telework potential have been made in the national and regional level. There is shortage of these measurements in different municipalities. The purpose of this article is to study the attitude of Latvian people with regard to telework adoption in two municipalities: Limbazi and Balvi in Latvia. Scientists indicate a positive effect of the information and communication technology (ICT) on the local economy if it is integrated into rural economy relating with needs of entrepreneurs and inhabitants (Grimes, 2000). Scientifi c methods of qualitative analysis of documents and such methods of quantitative analysis like statistical data and analyses of questionnaires have been used there. Observation and questionnaires were used in conjunction with the literature to develop an understanding of the infl uencing issues. Questionnaires ensure information about frequency of telework, willingness to do remote work and about benefi ts and barriers of teleworking in the rural areas and towns. The research reveals development possibilities of rural territories relying on higher involvement of ICT and knowledge economy. The main fi ndings are revealing signifi cant challenges faced by rural territories in a globalized world as the number of jobs in agriculture and public services is decreasing. It is important to develop not only agricultural activities but to provide other kinds of entrepreneurship with jobs physically (providing transport possibilities) or virtually (providing ICT). Results. 81% percent of the responding persons positively evaluate opportunity of telework. It reveals willingness of the people to do remote work as an alternative form of the existing work form. The largest interest (30%) about telework was shown in the age group of 31 – 40 in Limbazi municipality but the largest interest (26%) about telework in Balvi municipality was shown in the age group of 18 – 30. A significant percentage of the responding persons, 82% have the necessary computer abilities and knowledge on this topic. The majority of respondents is willing and is able to do telework taking into account the specifics of telework. The distribution of responses reveals that (52%) respondents are willing to use the premises of telecentres. In result the clients of the telecentres are not obliged to invest money into personal computers, multifunctional equipment and into different computer programs at home. When teleworking is offered, 77% of the respondents are interested to work from home but 14% prefer to work in a telecentre. When analysing the respondents’ answers about available services in the telecentre they indicate the most important services for them: copying, printing, scenery, accessibility of computer and the Internet-equipped working place. They are also interested in socializing and networking activities. They are also interested to receive some advice about entrepreneurship, job vacancies etc. Integration of telecentres in the territory helps to save commuting time. This is important for 52% percent of the responding persons. 34% percent of the responding persons would be able to save from 30 min to 1 hour of commuting time, 34% of the responding persons would be able to save more than 1 hour, 21% of the responding persons would be able to save less than 1/2 hour. Respondents indicate the economical and personal benefits as the main benefits of telework. 56% of the respondents indicate personal benefits to be the most important. They have more time for family, flexible working time. However, 39% of the respondents emphasised economic benefits as the most important, for example, less transport costs. Conclusions. 1. Rural territories face significant challenges in a globalized world as the number of jobs in agriculture and public services is decreasing. At the same time, information and communication technologies, as well as changes in professional duties allow the community from these regions to participate in the knowledge economy. The importance of virtual accessibility will grow when the costs of energy resources and transport are rising. Telework ensure possibility to involve disabled people in the labour market. 2. Involvement of remote work could improve accessibility of jobs in towns for people living in the rural areas using ICT and in such way partly or completely resolving internal and external migration problems. It brings benefits for municipalities, inhabitants and for entrepreneurs as well. Implementation of telework and telecentre in the territory can improve the assessment of a definite region from the working age people. It becomes more attractive place for living and staying there. 3. There are direct and indirect benefits from telework and telecentres as follows: reduction of expenditures like reduction of fuel and fuel expenditures, expenditures of car parking in the city or transport expenditures, the reduction of commuting time. It influences opportunity for cost reduction and growth of productivity if individual uses the saved time alternatively and productively. There are social benefits too, e.g. elastic working time, de-reutilization of work, reduction of external effects, e.g. the reduction of noise and stress in the office, increase in mentoring opportunities, more time for family and friends, hobbies, improved work/life balance, the possibility of living in rural areas while retaining challenging jobs in the knowledge economy traditionally linked to metropolis etc. 4. Participation by community members would increase through the use of telecentres. The main factors are the development of ICT and its infrastructure, wider use of ICT, changes in professional duties allow the community from these regions to participate in the knowledge economy. Promoting factor for entrepreneurs is cost saving, lowering of costs as follows: furniture purchase, ICT, programmes, public utilities payment, staff training and rent. Telework approach helps company to attract good, high motivated staff even with better qualification.